Hydrotalcite compound, resin composition and resin molded product

A hydrotalcite compound with controlled interlayer water content addresses thermal instability in chlorine-containing resins, enhancing thermal stability and preventing foaming and coloring.

JP7620697B2Active Publication Date: 2025-01-23SETOLAS HLDG INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023512864
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-06
Filing Date
2022-03-02
Publication Date
2025-01-23
Estimated Expiration
2042-03-02

AI Technical Summary

Technical Problem

Chlorine-containing resins suffer from low thermal stability, leading to issues such as foaming and coloring during processing and aging, which degrade product quality.

Method used

A hydrotalcite compound with specific X-ray diffraction and FT-IR characteristics is used, containing divalent and trivalent metal cations and anions, with controlled interlayer water content to enhance thermal stability.

Benefits of technology

The hydrotalcite compound effectively suppresses foaming and coloring by maintaining interlayer water balance, ensuring excellent thermal stability in resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620697000004
    Figure 0007620697000004
  • Figure 0007620697000005
    Figure 0007620697000005
  • Figure 0007620697000006
    Figure 0007620697000006
Patent Text Reader

Abstract

Provided is a hydrotalcite compound that can achieve superior thermal stability. A hydrotalcite compound according to an embodiment of the present invention is represented by general formula (I), and in an X-ray diffraction (XRD) pattern using Cu-Kα radiation, has two peaks attributed to (003) diffraction in the range where the diffraction angle 2θ is greater than or equal to 10° and less than or equal to 14°. The ratio RXRD(SP2 / SP1) of the area intensity of a second peak P2 to the area intensity of a first peak P1 is greater than or equal to 0.7 and less than or equal to 50, said second peak P2 having a peak top in the range where the diffraction angle 2θ is greater than 12° and less than or equal to 14°, and said first peak P1 having a peak top in the range where the diffraction angle 2θ is greater than or equal to 10° and less than or equal to 12°. (I): (M2+)1–X(M3+)X(OH)2(An–)X / n∙mH2O In formula (I), M2+ is a divalent metal cation, M3+ is a trivalent metal cation, An– is an n-valent anion, X satisfies 0.1≤X<0.4, n is an integer from 1 to 6, and m satisfies 0<m≤10.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydrotalcite compound, a resin composition, and a resin molded article. [Background technology]

[0002] Chlorine-containing resins are used in various products such as containers, pipes, and insulating materials due to their high processability and functionality. However, chlorine-containing resins have a problem in that they have low thermal stability and the quality of the product deteriorates during processing, aging, and the like. Specifically, there is a problem in that the appearance of the product is impaired due to foaming and coloring. To address this problem, the addition of hydrotalcite compounds has been proposed (for example, Patent Document 1). However, further improvement in thermal stability is required. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-178966 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in order to solve the above problems, and one of its objects is to provide a hydrotalcite compound that can achieve excellent thermal stability. [Means for solving the problem]

[0005] According to an embodiment of the present invention, a hydrotalcite compound is provided. This hydrotalcite compound is represented by the following general formula (I) and has two peaks attributed to (003) diffraction in the X-ray diffraction (XRD) pattern by Cu-Kα rays, with the diffraction angle 2θ in the range of 10° or more and 14° or less. The ratio R of the area intensity of the second peak P2 having a peak top in the range where the diffraction angle 2θ exceeds 12° and is 14° or less to the area intensity of the first peak P1 having a peak top in the range where the diffraction angle 2θ is 10° or more and 12° or less XRD (S P2 / S P1 ) is 0.7 or more and 50 or less: (M 2+ ) 1-X (M 3+ ) X (OH)2(A n- ) X / n ·mH2O···(I) In formula (I), M 2+ is a divalent metal cation, M 3+ is a trivalent metal cation, A n- is an n-valent anion, X satisfies 0.1 ≦ X < 0.4, n is an integer from 1 to 6, and m satisfies 0 < m ≦ 10. In one embodiment, the above hydrotalcite compound has a third peak P3 having a peak top in the range where the diffraction angle 2θ is 36° or more and 38° or less in the X-ray diffraction (XRD) pattern by Cu-Kα rays, and the ratio R XRD ’(S P3 / S P1 ) of the area intensity of the third peak P3 to the area intensity of the first peak P1 is 0.17 or more and 10 or less. In one embodiment, the above hydrotalcite compound has a first peak A1 in the range of 1270 cm -1 ~1460 cm -1 and a second peak A2 in the range of 1460 cm -1 ~1720 cm -1 in the FT-IR spectrum by the KBr tablet method, and the ratio R IR (S A2 / SA1 ) is 0.65 or more and 1.35 or less. In one embodiment, the hydrotalcite compound has substantially no peak or shoulder in the range of 2930 cm -1 ~3140 cm -1 in the FT-IR spectrum by the KBr tablet method. In one embodiment, in the above formula (I), X satisfies 0.2 ≦ X < 0.36, and m satisfies 0 < m ≦ 1.8.

[0006] According to another embodiment of the present invention, a resin composition is provided. This resin composition includes a resin containing a chlorine-containing resin and the above hydrotalcite compound. In one embodiment, 0.1 to 250 parts by weight of the hydrotalcite compound is contained per 100 parts by weight of the resin. According to still another embodiment of the present invention, a resin molded body is provided. This resin molded body is a resin molded body formed from the above resin composition.

[0007] According to still another embodiment of the present invention, a method for producing the above hydrotalcite compound is provided. This production method includes firing an unfired hydrotalcite compound in the atmosphere. In one embodiment, the firing is performed under the conditions that the firing temperature is 125°C or more and 300°C or less, and the firing time is 0.1 hour or more and 24 hours or less.

Advantages of the Invention

[0008] According to the present invention, the hydrotalcite compound has a predetermined area intensity ratio in the X-ray diffraction (XRD) pattern, so that excellent thermal stability can be achieved.

Brief Description of the Drawings

[0009] [Figure 1A] It is a diagram showing the X-ray diffraction patterns (diffraction angle 2θ: 5° to 70°) of the samples obtained in each example and comparative example. [Figure 1B]It is a figure showing the X-ray diffraction patterns (diffraction angle 2θ: 30° to 50°) of the samples obtained in each example and comparative example. [Diagram 2] It is a figure showing the FT-IR spectra of the samples obtained in each example and comparative example. [Diagram 3] It is the evaluation result of the thermal stability (foaming) of the samples obtained in each example and comparative example. [Figure 4] It is the evaluation result of the thermal stability (coloring) of the samples obtained in each example and comparative example.

Mode for Carrying Out the Invention

[0010] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0011] A. Hydrotalcite-like compounds The hydrotalcite-like compound in one embodiment of the present invention is represented by the following general formula (I). (M 2+ ) 1-X (M 3+ ) X (OH)2(A n- ) X / n ·mH2O···(I) In formula (I), M 2+ is a divalent metal cation, M 3+ is a trivalent metal cation, A n- is an n-valent anion, X satisfies 0.1 ≦ X < 0.4, n is an integer from 1 to 6, and m satisfies 0 < m ≦ 10. Preferably, in formula (I), X satisfies 0.2 ≦ X < 0.36. Preferably, in formula (I), m satisfies 0 < m ≦ 1.8.

[0012] In the above general formula (I), M 2+ is, for example, Mg 2+ , Zn 2+ , Ca 2+ , Sr 2+ , Cu 2+ , Fe 2+ , Mn 2+ , Co 2+ , Ni 2+, Sn 2+ , Pb 2+ , Cd 2+ and Ba 2+ At least one divalent metal ion selected from the group consisting of M 2+ is preferably Mg 2+ and Zn 2+ At least one divalent metal ion selected from the group consisting of, more preferably, Mg 2+ It is.

[0013] In the above general formula (I), M 3+ For example, Al 3+ , Fe 3+ , Cr 3+ , Co 3+ and In 3+ At least one trivalent metal ion selected from the group consisting of M 3+ is preferably Al 3+ This is because, for example, it is highly safe for living organisms, and the obtained hydrotalcite-based compound is white and can be applied to various uses.

[0014] In the above general formula (I), A n- For example, CO3 2- , SO4 2- , Cl - , SiO3 2- , PO4 3- , NO3 - , O.H. - , I - , (COO)2 2- , (CHOHCOO)2 2- , (CHOH)4CH2OHCOO - , C2H4(COO)2 2- , (CH2COO)2 2- , CH3CHOHCOO - , CH3PO4 2- , C2O4 2- , H.C.O.O. - , CH3COO - , CH3SO3 - , SiO3 2- , Si2O5 2- , SiO7 2- , Si4O92- , (HSiO3) - , (HSi2O5) - , HPO4 2- , PO4 3- and P2O7 4- At least one anion selected from the group consisting of n- is preferably CO3 2- It is.

[0015] A-1.Physical properties The hydrotalcite-based compound has two peaks attributable to (003) diffraction in the range of diffraction angle 2θ of 10° to 14° in its X-ray diffraction (XRD) pattern using Cu-Kα radiation. Specifically, it has a first peak P1 having a peak top in the range of diffraction angle 2θ of 10° to 12° and a second peak P2 having a peak top in the range of diffraction angle 2θ of more than 12° to 14°. Thus, the hydrotalcite-based compound having the first peak P1 and the second peak P2 has a shorter interlayer distance than the hydrotalcite-based compound having only the first peak P1, and it is considered that a part of the water (interlayer water) located between the layers is dehydrated and a part of the interlayer water remains.

[0016] The ratio R of the area intensity of the second peak P2 to the area intensity of the first peak P1 XRD (S P2 / S P1 ) is 0.7 or more, preferably 0.8 or more, more preferably 1 or more, and even more preferably 1.2 or more. XRDis 50 or less, preferably 30 or less, more preferably 25 or less, further preferably 21 or less, and particularly preferably 10 or less. According to such a range, foaming can be suppressed extremely effectively. Specifically, foaming caused by the interlayer water of the hydrotalcite compound can be suppressed by dehydrating a part of the interlayer water. At the same time, the chloride ion trapping ability of the hydrotalcite compound can be maintained by leaving a part of the interlayer water, and foaming caused by hydrochloric acid derived from the dehydrochlorination reaction of the resin can be suppressed, for example. When the chloride ions are not trapped by the hydrotalcite compound, the hydrochloric acid derived from the dehydrochlorination reaction of the resin can neutralize with the surface of the hydrotalcite compound, and water can be generated. This water can be evaporated to cause foaming. According to the above range, coloring caused by metal ions eluted from the hydrotalcite compound by the neutralization reaction can also be suppressed. One of the features of the present invention is that the neutralization reaction is focused on.

[0017] The hydrotalcite compound may have a third peak P3 having a peak top in a diffraction angle 2θ range of 36° to 38° in the XRD pattern by Cu-Kα radiation. The third peak P3 may be caused by alumina. The ratio R of the area intensity of the third peak P3 to the area intensity of the first peak P1 is XRD '(S P3 / S P1 ) is preferably 0.17 or more, more preferably 0.19 or more, and even more preferably 0.22 or more. XRD is preferably 10 or less, more preferably 8 or less, further preferably 5 or less, and particularly preferably 3 or less.

[0018] Hydrotalcite compounds have a peak at 1270cm in the FT-IR spectrum measured by the KBr pellet method. -1 ~1460cm -1 The first peak A1 and 1460 cm -1 ~1720cm -1 The ratio R of the area intensity of the second peak A2 to the area intensity of the first peak A1 may be in the range ofIR (S A2 / S A1 ) is preferably 0.65 or more, more preferably 0.7 or more. By dehydrating a part of the interlayer water which bears the hydrogen bond with the carbonate ion, the C=O double bond of the carbonate ion becomes high, and the intensity of the high wavenumber peak (A2) derived from the carbonate ion can be increased. IR (S A2 / S A1 ) can suppress foaming extremely effectively. In addition, by adopting a state in which the C=O double bond is high, for example, the interaction between the carbonate ion and the aluminum ion on the layer surface is increased, and it is thought that the water molecules that enter the interlayer due to moisture absorption after the interlayer water is dehydrated do not form hydrogen bonds, which can contribute to improving foaming suppression. IR is preferably 1.35 or less, more preferably 1.25 or less, further preferably 1.2 or less, and particularly preferably 1.1 or less. IR According to this, the carbonate ion exchange capacity between the layers can be maintained.

[0019] Hydrotalcite compounds have a peak at 2930cm in the FT-IR spectrum measured by the KBr pellet method. -1 ~3140cm -1 It is preferable that the sample has substantially no peak or shoulder within the above range. Specifically, it is preferable that a part of the interlayer water responsible for the hydrogen bonds is dehydrated. Here, "substantially no peak or shoulder" means that the deviation from the baseline is equal to or less than the noise level.

[0020] The hydrotalcite-based compound is typically in the form of particles. The average secondary particle diameter of the hydrotalcite-based particles is, for example, 0.1 μm to 3 μm, and preferably 0.2 μm to 1.5 μm. The average secondary particle diameter is the average value of the median diameter in particle size distribution measurement. The BET specific surface area of ​​the hydrotalcite-based particles is, for example, 5 m 2 / g~50m 2 / g, preferably 5m 2 / g~30m 2 / g.

[0021] In one embodiment, the hydrotalcite particles have a uniform composition throughout the particles (excluding the surface treatment agent when the surface treatment described below is performed). This embodiment can provide excellent production efficiency. Specifically, the number of production steps can be reduced compared to the case of using a core-shell structure.

[0022] A-2. Surface treatment The hydrotalcite particles are preferably surface-treated. Specifically, the hydrotalcite particles are preferably surface-treated using any appropriate surface treatment agent. For example, this is because the hydrotalcite particles can have excellent dispersibility when blended in a resin.

[0023] Examples of the surface treatment agent include higher fatty acids, alkali metal salts of higher fatty acids, anionic surfactants, cationic surfactants, silane coupling agents, titanate coupling agents, aluminum coupling agents, silicone treatment agents, water glass, silicic acid, phosphoric acid esters, esters of polyhydric alcohols and fatty acids, and sulfates of higher alcohols. These can be used alone or in combination of two or more. Among these, higher fatty acids are preferably used. As the higher fatty acid, at least one selected from the group consisting of lauric acid, oleic acid, and stearic acid is preferably used.

[0024] The amount of the surface treatment agent used is preferably 0.01% by weight to 20% by weight, more preferably 0.05% by weight to 15% by weight, further preferably 0.1% by weight to 10% by weight, and particularly preferably 0.5% by weight to 5% by weight, of the hydrotalcite particles.

[0025] A-3. Manufacturing method The hydrotalcite-based compound can be produced by any appropriate method, for example, by calcining (semi-calcining) an uncalcined hydrotalcite-based compound under predetermined conditions in the atmosphere.

[0026] The uncalcined hydrotalcite compound can be synthesized by any appropriate method. The reaction product obtained by a well-known and conventional method can be synthesized by heat-treating the reaction product in an aqueous medium. The reaction product can be obtained, for example, by reacting a metal salt such as magnesium or aluminum in an aqueous solution containing carbonate ions under a condition of pH 8.5 to 11.5. Details of the method for producing the uncalcined hydrotalcite compound (hydrotalcite particles) are described, for example, in International Publication No. 2015 / 068312. The entire disclosure of this publication is incorporated herein by reference. The surface treatment is preferably performed on the uncalcined hydrotalcite compound.

[0027] The calcination conditions of the uncalcined hydrotalcite compound can be set to any appropriate conditions as long as the above physical properties are satisfied. The calcination temperature of the uncalcined hydrotalcite compound is, for example, 125°C or higher, and preferably 180°C or higher. At such a temperature, the interlayer water can be efficiently dehydrated. On the other hand, the calcination temperature is, for example, 300°C or lower, and preferably 250°C or lower. At such a temperature, a hydrotalcite compound with a stable three-dimensional structure can be obtained.

[0028] The calcination time of the uncalcined hydrotalcite compound can be set, for example, according to the calcination temperature. Specifically, when the calcination temperature is high, the calcination time can be set short, and when the calcination temperature is low, the calcination time can be set long. The calcination time is, for example, 0.1 hours or more, and preferably 0.5 hours or more. On the other hand, the calcination time is, for example, 24 hours or less, and preferably 12 hours or less. In one embodiment, the calcination is performed at a temperature of 200° C. or more and 220° C. or less for 1 hour to 8 hours.

[0029] The calcination of the uncalcined hydrotalcite compound may be carried out continuously or in multiple stages at different temperatures. For example, the first calcination may be carried out at 200° C. to 210° C., and then the second calcination may be carried out at 180° C. to 190° C. In the case of carrying out the calcination in multiple stages, the above calcination time is the total of the calcination times in each stage.

[0030] A-4.How to use The hydrotalcite-based compound is typically contained in a resin (including rubber). Hereinafter, a resin composition containing a resin and a hydrotalcite-based compound will be described.

[0031] B. Resin composition The resin composition in one embodiment of the present invention includes a resin containing a chlorine-containing resin and the above-mentioned hydrotalcite compound. As the chlorine-containing resin, any appropriate resin can be used as long as it is a resin (polymer) containing chlorine atoms. Preferably, a vinyl chloride resin is used.

[0032] Examples of the vinyl chloride resin include homopolymers such as polyvinyl chloride (PVC), chlorinated polyvinyl chloride, polyvinylidene chloride, and chlorinated rubber. Also included are copolymers such as vinyl chloride-vinyl acetate copolymer, vinyl chloride-ethylene-vinyl acetate copolymer, vinyl chloride-ethylene copolymer, vinyl chloride-propylene copolymer, vinyl chloride-styrene copolymer, vinyl chloride-isobutylene copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-urethane copolymer, vinyl chloride-acrylic acid ester copolymer, vinyl chloride-styrene-maleic anhydride copolymer, vinyl chloride-styrene-acrylonitrile copolymer, vinyl chloride-butadiene copolymer, vinyl chloride-isoprene copolymer, vinyl chloride-chlorinated propylene copolymer, vinyl chloride-vinylidene chloride-vinyl acetate copolymer, vinyl chloride-maleic acid ester copolymer, vinyl chloride-methacrylic acid ester copolymer, vinyl chloride-acrylonitrile copolymer, vinyl chloride-maleimide copolymer, and internally plasticized polyvinyl chloride.

[0033] The resin may include a chlorine-free resin. Examples of the chlorine-free resin include thermoplastic resins such as polyethylene, copolymers of ethylene and other α-olefins, ethylene-vinyl acetate copolymers, ethylene-acrylic acid ether copolymers, ethylene-methyl acrylate copolymers, polypropylene, copolymers of propylene and other α-olefins, polybutene-1, poly4-methylpentene-1, polystyrene, styrene-acrylonitrile copolymers, ethylene-propylene diene rubber copolymers, ethylene-butadiene copolymers, polyvinyl acetate, polylactic acid, polyvinyl alcohol, polyacrylate, polymethacrylate, polyurethane, polyester, polyether, polyamide (PA), acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate (PC), polyphenylene sulfide (PPS), and polyacetal (POM). Examples of the thermosetting resins include phenolic resins, melamine resins, epoxy resins, unsaturated polyester resins, and alkyd resins. Examples of non-chlorine-containing resins (rubbers) include ethylene-propylene-diene rubber (EPDM), hydrogenated nitrile rubber (HNBR), natural rubber (NR), butadiene rubber (BR), urethane rubber (U), styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), butyl rubber (IIR), isoprene rubber (IR), and silicone rubber (Q).

[0034] In the above resin composition, the hydrotalcite compound is preferably contained in an amount of 0.1 to 250 parts by weight, more preferably 1 to 200 parts by weight, and even more preferably 1 to 100 parts by weight, per 100 parts by weight of the resin.

[0035] The resin composition may contain optional components. Examples of the optional components include heat stabilizers, plasticizers, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, colorants, color inhibitors, and impact modifiers. These may be used alone or in combination of two or more.

[0036] The heat stabilizer is preferably contained in an amount of 0.01 to 10 parts by weight relative to 100 parts by weight of the resin. The plasticizer is preferably contained in an amount of 1 to 70 parts by weight relative to 100 parts by weight of the resin. The antioxidant is preferably contained in an amount of 0.01 to 2 parts by weight relative to 100 parts by weight of the resin. The ultraviolet absorber is preferably contained in an amount of 0.01 to 3 parts by weight relative to 100 parts by weight of the resin. The antistatic agent is preferably contained in an amount of 0.01 to 2 parts by weight relative to 100 parts by weight of the resin. The lubricant is preferably contained in an amount of 0.1 to 5 parts by weight relative to 100 parts by weight of the resin. The colorant is preferably contained in an amount of 0.1 to 2 parts by weight relative to 100 parts by weight of the resin. The coloring inhibitor is preferably contained in an amount of 0.01 to 5 parts by weight relative to 100 parts by weight of the resin. The impact modifier is preferably contained in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the resin.

[0037] The hydrotalcite-based compounds include, for example, perchloric acid-containing hydrotalcite-based compounds, perchlorates such as perchlorates, organotin compounds, magnesium hydroxide (for example, a compound having a BET specific surface area of ​​15 m 2 / g or more and an average secondary particle size of 2 μm or less), magnesium oxide (for example, a BET specific surface area of ​​50 m 2 / g or more, it is possible to suppress the use of stabilizers such as fine particle-shaped highly active magnesium oxide. Specifically, the content of the stabilizer is, for example, 5 parts by weight or less, preferably 1 part by weight or less, more preferably 0.1 parts by weight or less, further preferably 0.01 parts by weight or less, and particularly preferably 0.001 parts by weight or less, relative to 100 parts by weight of the resin.

[0038] C. Resin molded body The resin molded article in one embodiment of the present invention is formed from the resin composition. Specifically, the resin molded article contains the resin and the hydrotalcite compound. EXAMPLES

[0039] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows, unless otherwise specified. 1.Average secondary particle size The measurement was performed using a MICROTRAC particle size distribution analyzer (NIKKISO Corporation, MT3000II series). Specifically, 5 ml of methanol was mixed with 700 mg of sample (powder), and then 70 mL of 2.0 g / L sodium hexametaphosphate aqueous solution was added thereto, followed by ultrasonic treatment for 3 minutes (using a Nissei Corporation "MODEL US-300" at a current of 400 μA). Then, 2 to 4 mL of the obtained dispersion was added to the sample chamber of the particle size distribution analyzer, which contained and circulated 220 mL of degassed sodium hexametaphosphate aqueous solution (2.0 g / L), and the particle size distribution was measured after circulating the dispersion for 1 minute. A total of two measurements were performed, and the average value of the 50% cumulative secondary particle diameters (median diameters) obtained in each measurement was calculated to obtain the average secondary particle diameter. 2.Specific surface area The measurements were made using a high-precision gas adsorption measurement device (Microtrack-Bell's "BELsorp-max"). Specifically, measurements were made using a constant-volume gas adsorption method using nitrogen gas, and the specific surface area was calculated using the BET multipoint analysis method. 3.Mg / Al2 molar ratio The sample (powder) was dissolved in acid, and the Mg and Al contents in the resulting solution were quantified by chelate titration to calculate the Mg / Al2 molar ratio.

[0040] [Example 1] In a 1L reaction vessel, while stirring a certain amount of ion-exchanged water, 160mL of 1.5mol / L magnesium chloride aqueous solution, 120mL of 1mol / L aluminum chloride aqueous solution, and a mixed solution of 90mL of 8mol / L sodium hydroxide aqueous solution and 60mL of 1mol / L sodium carbonate aqueous solution were simultaneously poured into the vessel to obtain a reaction product. The pH during the reaction was 9.5. The resulting reaction product (700 mL) was subjected to solid-liquid separation using a Nutsche filter, the resulting solid was washed with ion-exchanged water, and then ion-exchanged water was added again to obtain 700 mL of re-emulsified slurry. The resulting re-emulsified slurry (700 mL) was subjected to hydrothermal treatment at 170°C for 13 hours and cooled. The resulting slurry was then heated to 80°C, and an aqueous solution (80°C) of 0.55 g of sodium stearate was gradually added to the slurry under stirring, and this state was maintained for 30 minutes. The solid obtained by solid-liquid separation using a Nutsche filter was then washed with 800 mL of ion-exchanged water and dried at 105°C for 18 hours. The resulting dried product was pulverized using a hammer mill and then sieved through a 150 micron filter to obtain a powder. The obtained powder had an average secondary particle size of 0.58 μm and a BET specific surface area of ​​8.1 m 2 The molar ratio of Mg / Al2 was 4.00. The chemical formula of the powder was Mg / g and the Mg / Al2 molar ratio was 4.00. 0.66 Al 0.33 (OH)2(CO3) 0.16 ·0.50H2O and satisfies the above general formula (I).

[0041] 40 g of the obtained powder was placed in a stainless steel tray (20.6 cm × 16.6 cm × 2.7 cm) and thoroughly loosened with a stainless steel spoon to obtain a powder density of 0.17 g / cm. 3 The powder was baked at 210°C for 2 hours (powder thickness: 1 cm). The tray was then placed in a constant temperature incubator (DKN602 model, manufactured by Yamato Scientific Co., Ltd.) that had been preheated to 210°C, and after the tray was placed in, the temperature reached 210°C and the tray was baked in air at the same temperature for 2 hours. After baking, the tray was removed from the incubator, and without cooling, the powder was immediately placed in a mayonnaise jar and stored in a desiccator. Thus, the sample of Example 1 (BET specific surface area: 12.41 m) was obtained. 2 / g, Mg / Al2 molar ratio was 4.00, satisfying the above general formula (I).

[0042] [Example 2] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 215° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, which satisfies the above general formula (I).

[0043] [Comparative Example 1] Except for not carrying out the calcination, a sample was obtained in the same manner as in Example 1. The obtained powder had an Mg / Al2 molar ratio of 4.00 and satisfied the above general formula (I).

[0044] [Comparative Example 2] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 195° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, which satisfies the above general formula (I).

[0045] [Comparative Example 3] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 200° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, which satisfies the above general formula (I).

[0046] [Comparative Example 4] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 203° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, which satisfies the above general formula (I).

[0047] [Comparative Example 5] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 207° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, satisfying the above general formula (I).

[0048] [Comparative Example 6] A sample was obtained in the same manner as in Example 1, except that the firing temperature was 220° C. The obtained powder had an Mg / Al2 molar ratio of 4.00, which satisfies the above general formula (I).

[0049] [Comparative Example 7] A sample (BET specific surface area: 11.66 m) was prepared in the same manner as in Example 1, except that the calcination temperature was 250° C. 2 The resulting powder had a Mg / Al2 molar ratio of 4.00, but water was completely removed, and the powder did not satisfy the above general formula (I).

[0050] The samples obtained in each of the Examples and Comparative Examples were measured for the following items. The measurement results are shown in Figures 1-A and 1-B and Table 1. 1. X-ray diffraction measurement The obtained sample powder was placed in a glass cell for X-ray measurement, and the sample surface was flattened with a glass plate to obtain a sample for measurement. Then, measurement was performed using EMPYREAN (manufactured by PANalytical BV) to obtain an X-ray diffraction pattern. The measurement conditions were as follows. ·X-ray source: Cu-Kα ray (λ=1.542Å) Voltage: 45kV ·Current: 40mA Goniometer: Horizontal goniometer (reflection mode) Step angle: 0.013° Scan speed: 9.8° / min Diffraction angle 2θ: 5°~70° 2. Area intensity ratio of X-ray diffraction peaks Using X-ray diffraction software High Score Plus (PANalytical BV), baseline correction was performed for the diffraction angle 2θ of 5° to 70° of the obtained X-ray diffraction pattern. Then, peaks attributable to the (003) diffraction of hydrotalcite-based compounds were specified in the range of diffraction angle 2θ of 10° to 14°, and profile fitting was performed with the asymmetric function "split width and shape". After analysis, the peak having a peak top in the range of diffraction angle 2θ of 10° to 12° was designated as the first peak P1, and the peak having a peak top in the range of diffraction angle 2θ of more than 12° to 14° was designated as the second peak P2, and the area intensity (S P1 , S P2 [counts*°2θ]) gives the ratio R of the area intensity of the second peak P2 to the area intensity of the first peak P1. XRD (S P2 / S P1 Similarly, a peak having a peak top in the range of a diffraction angle 2θ of 36° to 38° was designated as a third peak P3, and the area intensity S P3 From the above, the ratio R of the area intensity of the third peak P3 to the area intensity of the first peak P1 is XRD '(S P3 / S P1 ) was calculated.

[0051] [Table 1]

[0052] The samples obtained in each of the Examples and Comparative Examples were measured for the following items. The measurement results are shown in FIG. 3.FT-IR Measurement The measurement was performed using the KBr pellet method. 2 mg of sample powder and 20 mg of KBr, which had been dried at 120°C and cooled in a desiccator, were ground in a mortar with a pestle. The obtained powder was then molded into a φ5 mm ClearDisk using a ClearDisk molding machine (manufactured by Jusco Engineering Co., Ltd.) and a mini hand press MP-1MiniPress (manufactured by Jusco Engineering Co., Ltd.). In the same manner, a ClearDisk containing only 20 mg of KBr was molded for background measurement. The obtained ClearDisk was set in a ClearDisk holder of an infrared spectrophotometer (FT / IR-4100, manufactured by JASCO Corporation) and measured at room temperature and normal pressure under the following measurement conditions. Detector: TGS ·Resolution: 4cm -1 Measurement range: 400cm -1 ~4000cm -1 Number of times accumulated: 64 4. FT-IR peak area intensity ratio The spectrum was measured and analyzed using the SpectraManager spectrum measurement and analysis software (JASCO Corporation). The horizontal axis is the wave number (cm -1 ), and the vertical axis is the transmittance (%T). After atmospheric correction (CO2 subtraction, water vapor subtraction), the spectrum was smoothed (method: Savitzky-Golay, convolution width: 15). -1 and 3550cm -1 The peak valley (minimum value) located between 4000 cm and 4000 cm -1The difference between the transmittance of -1 , 2500cm -1 , 4000cm -1 The transmittance of the three points was normalized to 80. After normalization, the signal was detected at a noise level of >0.5 and was detected at 1270 cm -1 ~1460cm -1 The peaks in the range of 1460 cm are the first peak A1 and 1460 cm -1 ~1720cm -1 The peak within the range is the second peak A2, and the peak at 1270 cm detected at a noise level of 1.0 is the second peak A3. -1 ~1720cm -1 The maximum point of 1270 cm on the spectrum -1 Or 1720cm -1 The straight line connecting these points was taken as the baseline for A1 and A2. The areas enclosed by each baseline and spectrum are the area intensities S of A1 and A2, respectively. A1 , S A2 The ratio R of the area intensity of the second peak A2 to the area intensity of the first peak A1 is IR (S A2 / S A1 ) was calculated.

[0053] [Table 2]

[0054] From FIG. 2, in Examples 1 and 2 and Comparative Examples 6 and 7, -1 ~3140cm -1 It is confirmed that the linearity of the saturation peak does not substantially have a peak or shoulder within the range of 1.

[0055] <Evaluation> The thermal stability of the samples obtained in each of the Examples and Comparative Examples was evaluated by the following method. 1. Foaming 100 parts by weight of PVC (TK-700, manufactured by Shin-Etsu Chemical Co., Ltd.; vinyl chloride resin, degree of polymerization 700), 0.6 parts by weight of Zn-st (zinc stearate, manufactured by NOF Corp.; lubricant and heat stabilizer), 0.6 parts by weight of Ca-st (calcium stearate, manufactured by NOF Corp.; lubricant and heat stabilizer), 0.2 parts by weight of SBM (stearoyl benzoyl methane, manufactured by JIAXIAN; color inhibitor), 0.4 parts by weight of WAX OP (mixture of sodium maltate and calcium maltate, manufactured by Clariant; lubricant), 0.8 parts by weight of Castor wax (hardened castor oil, manufactured by Koster Keunem; lubricant) and 1.0 parts by weight of the obtained sample were kneaded at 190°C for 3 minutes using an open roll to obtain a resin sample. The obtained resin sample was heated and compressed at 230°C for 5 minutes in a compression molding machine to prepare a test piece with a length of 75 mm, a width of 25 mm, and a thickness of 2 mm, and the degree of foaming of the test piece was evaluated. Specifically, the obtained test piece was imaged as shown in Figure 3, and the proportion of the area corresponding to foaming in the obtained image of a specified size (foaming proportion R RESIN The evaluation results are shown in Table 3 together with the firing temperatures. The evaluation criteria for foaming are as follows: (Evaluation Criteria) Good: 0≦R RESIN ≦0.14 Slightly poor: 0.14 <R RESIN ≦0.23 Bad: 0.23 <R RESIN <= 1 2. Coloring A resin sample was obtained by kneading 100 parts by weight of PVC (TK-1300, manufactured by Shin-Etsu Chemical Co., Ltd.; vinyl chloride resin, degree of polymerization 1300), 50 parts by weight of DINP (diisononyl phthalate, manufactured by Daihachi Chemical Industry Co., Ltd.; plasticizer), 0.6 parts by weight of Zn-st (zinc stearate, manufactured by NOF Corporation; lubricant and heat stabilizer) and 3.0 parts by weight of the obtained sample at 200°C using a Plastomill at a rotation speed of 30 rpm. After kneading was completed, the resin samples were taken out of the kneading tank (200°C) every 5 minutes and the degree of coloring was observed. The observation results are shown in Figure 4 together with the baking temperature. The degree of coloring was also evaluated by measuring the Yellow Index with a color meter (ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.). The Yellow Index after 20 minutes of kneading (initial coloring) and the time at which the Yellow Index value exceeded 130 (coloring over time) are shown in Table 3. The evaluation criteria for coloring are as follows: (Evaluation criteria for initial coloration) Good: Yellow Index ≦ 60 Slightly poor: 60 <Yellow Index≦80 Defective: 80 <Yellow Index (Evaluation criteria for coloration over time) Good: 65 < time (minutes) Slightly poor: 40<time(min)≦65 Defective: Time (min) ≦ 40

[0056] [Table 3]

[0057] In Examples 1 and 2, the occurrence of foaming is remarkably suppressed. The foaming in Comparative Example 1, where no baking was performed, is believed to be mainly due to interlayer water and CO2 gas. The foaming in Comparative Examples 6 and 7, where the baking temperature was high, is mainly due to water generated by the neutralization reaction between hydrochloric acid derived from the dehydrochlorination reaction of the resin and the surface of the hydrotalcite compound, and interlayer CO3 2- This reaction is believed to be due to CO2 gas derived from the oxidized gas. This reaction can be confirmed by using the pH-stat method.

[0058] In Examples 1 and 2, coloring (initial coloring and coloring over time) was also well suppressed. The higher the baking temperature, the faster the coloring tends to occur. This is thought to be due to a decrease in the ability of the resin to capture chloride ions.

[0059] From the evaluation results of the foaming and coloring (initial coloring and coloring over time), the examples can be seen to have excellent thermal stability.

[0060] The above evaluation was also attempted for a resin sample to which no test material (powder) was added, but the sample turned black during molding due to thermal degradation and could not be evaluated. [Industrial Applicability]

[0061] The hydrotalcite compound in one embodiment of the present invention can be suitably combined with a chlorine-containing resin.

Claims

1. A particulate hydrotalcite compound, Represented by the following general formula (I): The particle has a uniform composition throughout, In an X-ray diffraction (XRD) pattern using Cu-Kα radiation, there are two peaks attributable to (003) diffraction in the range of a diffraction angle 2θ of 10° or more and 14° or less; The ratio R of the area intensity of the second peak P2 having a peak top in the range of the diffraction angle 2θ of more than 12° and not more than 14° to the area intensity of the first peak P1 having a peak top in the range of the diffraction angle 2θ of 10° or more and not more than 12° XRD (S P2 / S P1 ) is equal to or greater than 1.26 and equal to or less than 20.15; In an X-ray diffraction (XRD) pattern using Cu-Kα radiation, a third peak P3 has a peak top in a diffraction angle 2θ range of 36° or more and 38° or less, a ratio R XRD ′ (S P3 / S P1 ) of the area intensity of the third peak P3 to the area intensity of the first peak P1 is 0.29 or more and 4.82 or less; In the FT-IR spectrum by the KBr tablet method, it has a first peak A1 in the range of 1270 cm -1 to 1460 cm -1 and a second peak A2 in the range of 1460 cm -1 to 1720 cm -1 ; a ratio R IR (S A2 / S A1 ) of the area intensity of the second peak A2 to the area intensity of the first peak A1 is 0.83 or more and 1.24 or less; In the FT-IR spectrum measured by the KBr tablet method, the compound has substantially no peak or shoulder in the range of 2930 cm −1 to 3140 cm −1 . Hydrotalcite compounds: (M 2+ ) 1-X (M 3+ ) X (OH) 2 (A n- ) X/n ・mH 2 O・・・(I) In formula (I), M 2+ is Mg2+, M 3+ is Al 3+, and A n- is CO 3 2-, X satisfies 0.1≦X<0.4, n is an integer of 1 to 6, and m satisfies 0<m≦10.

2. 2. The hydrotalcite compound according to claim 1, wherein, in formula (I), X satisfies 0.2≦X<0.36, and m satisfies 0<m≦1.

8.

3. A resin including a chlorine-containing resin; The hydrotalcite compound according to claim 1 or 2. A resin composition comprising:

4. The resin composition according to claim 3, comprising 0.1 to 250 parts by weight of the hydrotalcite compound per 100 parts by weight of the resin.

5. A resin molded product formed from the resin composition according to claim 3 or 4.

6. 3. A method for producing a hydrotalcite-based compound according to claim 1, comprising calcining an uncalcined hydrotalcite-based compound in air.

7. The method according to claim 6, wherein the firing is carried out at a firing temperature of 125° C. or more and 300° C. or less for a firing time of 0.1 hours or more and 24 hours or less.

Citation Information

Patent Citations

  • HYDROTALCITE TYPE PARTICLE POWDER AND Mg-Al-BASED COMPOUND OXIDE PARTICLE POWDER, AND RESIN COMPOSITION CONTAINING THE HYDROTALCITE TYPE PARTICLE POWDER

    JP2011105573A

  • Zn-Mg-Al HYDROTALCITE TYPE PARTICLE POWDER AND RESIN COMPOSITION CONTAINING THE Zn-Mg-Al HYDROTALCITE TYPE PARTICLE POWDER

    JP2011178966A

  • Filler for synthetic resin, synthetic resin composition, manufacturing method therefor, and molded object made therefrom

    WO2011111487A1